7.0 Tesla MRI Brain White Matter Atlas - Cho, Zang-Hee (Springer Berlin Heidelberg : Imprint: Springer, 2015)
The introduction of techniques that permit visualization of the human nervous system is one of the foremost advances in neuroscience and brain-related research. Among the most recent significant developments in this respect are ultra-high field MRI and the image post-processing technique known as track density imaging (TDI). It is these techniques (including super-resolution TDI) which represent the two major components of 7.0 Tesla MRI - Brain White Matter Atlas. This second edition of the atlas has been revised and updated to fully reflect current application of these technological advancements in order to visualize the nervous system and the brain with the finest resolution and sensitivity. Exquisitely detailed color images offer neuroscientists, neurologists, and neurosurgeons a superb resource that will be of value both for the purpose of research and for the treatment of common brain diseases such as Alzheimer's disease and multiple sclerosis.